PENGARUH PENERAPAN MEDIA KUIS BERBASIS KAHOOT TERHADAP MINAT BELAJAR GEOGRAFI SISWA KELAS XI SMA NEGERI 1 SUNGAI PUAR KABUPATEN AGAM - Zurri Yati Khairi; Rery Novio (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to (1) Knowing the geographical factors that support the development of Pincuran Puti Tourism objects (2) Knowing the efforts made by the Solok Regency Government for the development of Pincuran Puti Tourism objects. The method used in this study is a descriptive method with a quantitative approach. The population in this study is all problems related to tourism activities which include several tourist attractions in Pincuran Puti, surrounding residents, tourist attractions, tourists and managers, The sample in this study consists of local communities and tourist attraction managers. The method of data collection is obtained from the data of observations, interviews and documentation. Data analysis techniques are in the form of tread analysis techniques. The results of this study show that (1) geographical factors that support the development of Pincuran Puti Tourism objects, namely slopes between 8%-15%, temperatures are at an average of 17.64 °C, podzolic / Red Yellow soil types used for plantations and rice fields, geology Nagari Talang Babungo Pincuran Puti Tourism including Upper Member Formations, Flora containing Fagus grandifolia, Junglans regial, Mangifera Indica L, Castanea sp. (2) efforts made by the solok district government for the development of Pincuran Puti Tourism objects can use both electronic and print media, building cross-sectoral moderation. Keywords : Descriptive, Site Analysis, Geographic Factors.